A commentary on gender bias in dermatology and its perceived impact on career development among women dermatologists() - DeWane, Madeline E. (Int J Womens Dermatol, 2020)
Gender bias and gender-based discrimination and harassment are known to affect women across all fields of medicine. Despite acknowledgement of a persistent “gender gap” in dermatology, there has been little formal research to date exploring how gender bias may be impacting the careers of women in the field. In this commentary, we discuss the results of an anonymous, online survey that assessed perceived effects of gender bias and sexual harassment on professional development among women dermatologists. The large majority of respondents reported experiencing significant gender-based obstacles to career advancement in either their current or past practice settings. Lack of equal professional support between men and women and discrimination based on parental status were commonly noted themes. A majority of respondents also reported having experienced some form of sexual harassment in the workplace. These trends, while not unique to the field of dermatology, are unacceptable and need to be confronted and rectified. Promoting gender equity in dermatology is important for clinicians, patients, and the future of dermatology.